EFEK PROGRAM PEMBERIAN "TABURIA" TERHADAP KADAR HEMOGLOBIN BALITA PADA KELUARGA MISKIN DI JAKARTA UTARA - Abas Basuni Jahari; Sri Prihatini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
Effect of "Taburia" Intervention Program on Hemoglobin Concentration Among Children Under-Five Years of Poor Families In North Jakarta.Background: Anemia is one of the main nutritional problems in Indonesia. Anemia in children under fives years will have an impact on growth and mental development. In an effort to improve the nutritional status of infants, especially in poor families, the Japan Funds for Poverty Reduction (JFPR) in collaboration with the Center for Nutrition and Food, Ministry of Health, Bogor, making multi-vitamin ingredients and micro nutrients called as TABURIA.Objectives: To study the influence of hemoglobin levels on child under fives years of poor families.Methods: Design of the study was Evaluation Before and After Treatment (Pre-Post Evaluation). This research was conducted in 9 urban villages in 3 Public health centers in North Jakarta City. The numbers of samples were 540 children aged 6-59 months from poor families. Tabuaria was distributed by a cadre posyandu to all children under fives years (5000 children) in the research area. The data analyzed included: hemoglobin levels, economic social family, compliance and child morbidity. Data were analyzed by descriptive to determine changes in status of anemia and haemoglobin levels before and after intervention.Results: Most of children under fives years (87.8%) to receive and consume Taburia. The average Hb levels increased from 10.5 mg/dl in baseline data to 12.0 mg/dl at endline evaluation. The proportion of anemia (Hb <11 mg/dl) decreased significantly from 62.3% (baseline) to 24.7%(endline-evaluation).Conclusion: Taburia be accepted by the majority of children under fives and can increase hemoglobin levels of children under fives.Recommendation: Taburia can increase the hemoglobin levels of children under fives years, but if would be implemented as national program, it should be study in others regions (pilot areas) to explore the appropriateness Taburia distribution model in different conditions.Keywords: taburia, hemoglobin levels, poor families